Mirror, Mirror on the Wall: The role of reflective practice in architectural education at Curtin University - MackIntosh, Lara (Black Swan Press, 2013)
Current architectural practice has contributed to our changing world. In order to mitigate and adapt to the impact of those changes, the architectural profession is required to shift their approach to design, and to reconsider their responsibilities. Despite recent technological advances, there is little evidence of the change in attitude amongst architecture students and practitioners toward embracing sustainable design. As part of a larger research project investigating the role of architectural education in long term sustainable behaviour, a study was conducted to develop a method of interpreting the outcomes of a transformative learning experience. Architectural students in their final semester of the undergraduate program at Curtin University were asked to consider their everyday activities, personal attitudes, and design practices as they completed a series of reflective tasks. This paper examines the methodology of this study, and discusses the role of critical and self-reflection in transformative learning.